Analisis Resiko Keamanan Pada E-Commerce Shopee Terhadap Kenyamanan Konsumen Menggunakan Metode Kualitatif - Muhamad Ginanjar BayuAji P; Muhammad Hafizh Al Mustofa; Rizqi Saputra; Syaiful Nur Wardani (Fakultas Ilmu Komputer Universitas Duta Bangsa Surakarta, 2023)
In this digital era, of course there have been many technological developments that are increasingly rapidly affecting the business market, so companies are required to keep up with times. E-commerce has several advantages including transactions do not need to be face-to-face, save time, make transactions easier, and more efficient. Behind these advantages, e-commerce has disadvantages, namely that it can expose consumers to fraud, personal data can be leaked, the system can experience errors and so on. The author made this research to analyze what risks can occur on e-commerce websites using the description analysis method and the purpose of this writing is so that the public can find out the risks that can occur at Shopee, so as to minimize losses that occur to both consumers. Due to uncertainty, every individual or organization's actions must contain risks. There may be a risk that there may be a lot of lack of information about things that will happen in the future, both profitable and detrimental. With the problem of possible risks for Shopee consumers, the Sampling Technique uses Voluntary Sampling, which is one of the main types of sampling methods. non-probability sample. The voluntary sample consists of people who self-opted into the survey. With a total of 315 respondents, it can be concluded that the results of the respondents indicate that transactions can be trusted. feel confident in sharing personal information, responsive in resolving user complaints, so that Shopee is proven to optimize security, service and problem solving for its consumers.